Sistem Penjaminan Mutu Internal di SMP/MTs : Kajian Literatur Tentang Konsep dan Implementasi - Friska Ayu Nur Rabani; Ananda Annisa Amalia; Cindy Aprilia Ratnasari (Jurnal Pendidikan dan Kewarganegara Indonesia, 2024)
This study explores the implementation of the Internal Quality Assurance System (IQAS) at the junior high school level (SMP/MTs) through a literature review. The research aims to analyze the application of IQAS in achieving the Eight National Education Standards (NES). A qualitative descriptive method was employed, utilizing a literature study approach and data sourced from relevant journals, books, and policy documents. The findings indicate that implementing IQAS positively impacts the quality of learning and school management, supported by factors such as school leadership, stakeholder collaboration, and the availability of infrastructure. However, challenges remain, including limited understanding among educators and staff, inadequate facilities, and insufficient financial support. The study concludes that the success of IQAS implementation relies on the collaboration of all stakeholders and continuous evaluation. Recommendations include enhancing awareness of IQAS, strengthening human resource capacity, and optimizing the use of infrastructure.